Balaglitazone reverses P-glycoprotein-mediated multidrug resistance via upregulation of PTEN in a PPARγ-dependent manner in leukemia cells. Issue 10 (September 2017) - Yousefi, Bahman; Azimi, Ako; Majidinia, Maryam; Shafiei-Irannejad, Vahid; Badalzadeh, Reza; Baradaran, Behzad; Zarghami, Nosratollah; Samadi, Nasser
Multidrug resistance in tumor cells is still a big challenge in cancer treatment. Therefore, identification ofsafe and effective multidrug resistance–reversing compounds with minimal side effects is an important approach in cancer treatment. Here, we investigated the role and potential mechanisms of peroxisome proliferator–activated receptor γ in doxorubicin-resistant human myelogenous leukemia (K562/DOX) cells. The effect of doxorubicin on cell viability following treatment with balaglitazone, a peroxisome proliferator–activated receptor γ agonist, was evaluated using trypan blue and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assays. Rhodamine123 assay was used to determine the activity of two common drug efflux membrane transporters P-glycoprotein and multidrug resistance protein-1. P-glycoprotein, multidrug resistance protein-1, and phosphatase and tensin homolog deleted on chromosome 10 messenger RNA/protein expression levels were measured by quantitative reverse transcription polymerase chain reaction and western blot analyses. Annexin V/fluorescein isothiocyanate assay was also employed to investigate apoptosis. We showed that balaglitazone considerably enhanced the cytotoxicity of doxorubicin. Balaglitazone also significantly downregulated P-glycoprotein expression and activity in K562/DOX cells and reduced multidrug resistance through elevation of intracellular doxorubicin in cells. Furthermore, upon balaglitazone treatment, phosphatase and tensin homolog deleted on chromosome 10 expression could be restored in K562/DOX cells in a peroxisome proliferator–activated receptor γ–dependent manner. We concluded that peroxisome proliferator–activated receptor γ agonist, balaglitazone, could reverse multidrug resistance by inducing phosphatase and tensin homolog deleted on chromosome 10 and peroxisome proliferator–activated receptor/ phosphatase and tensin homolog deleted on chromosome 10 signaling pathway. These findings suggest that targeting peroxisome proliferator–activated receptor γ might serve as an effective approach for circumventing multidrug resistance in chemotherapy of cancerous patients.